INCREASING STUDENTS’ CREATIVITY AND WRITING SKILL THROUGH PjBL - Trisnaningsih, Widiani (Universitas Muhammadiyah Metro, 2017)
The objective of this research was to find out whether there was an increase on students’ and teacher’s activity, students’ creativity, and students’ writing skill through the implementation of project-based learning (PjBL). The research design was classroom action research. The subjects were the first graders of class Tata Kecantikan Kulit (TKK) or Skin and Beauty Treatment at Vocational High School State 3 Metro, known as SMKN 3 Metro, in the second semester, academic year 2015/2016. This action research was done by doing: 1) planning; 2) implementation; 3) observation and data collection; and 4) reflection. Meanwhile, the PjBL was done through six steps, i.e.: 1) determining the project; 2) planning the steps of doing the project; 3) scheduling the project implementation; 4) completing project with guide and supervision from the teacher; 5) making report and presenting project result; 6) evaluating process and project result. The instruments of this research were students and teacher observation, creativity assessment, and writing skill assessment. The findings showed that the students’ and teacher’s activity gradually increased in each cycle. PjBL implementation also seemed to be effective in increasing the students’ creativity and writing skill. It indicated that by applying PjBL, the aspects of students’ and teacher’s activity in learning process, students’ creativity and writing skill could be directly influenced by the treatment.